HBR's 10 must reads : on managing yourself. Vol. 2 - Kolb, Deborah M.; Cross, Rob.; Badaracco, Joseph L.; Roberts, Laura Morgan (La Vergne : Harvard Business Review Press, 2021)
From the preeminent thinkers whose work has defined an entire field to the rising stars who will redefine the way we think about business, here are the leading minds and landmark ideas that have established the Harvard Business Review as required reading for ambitious business people in organizations around the globe.
Intro -- Contents -- Ch. 1: From Purpose to Impact -- Ch. 2: Learning to Learn -- Ch. 3: Making Yourself Indispensable -- Ch. 4: Make Time for the Work That Matters -- Ch. 5: Collaboration without Burnout -- Ch. 6: Emotional Agility -- Ch. 7: How to Tackle Your Toughest Decisions -- Ch. 8: How Dual-Career Couples Make It Work -- Ch. 9: Cultivating Everyday Courage -- Ch. 10: Be Your Own Best Advocate -- Ch. 11: Building an Ethical Career -- Ch. 12: When and How to Respond to Microaggressions -- About the Contributors -- Index
Description based upon print version of record.
Added to collection customer.56279.3
Keywords: Management; Motivation (Psychology); elektronické knihy; electronic books